Development, validation and application of multi-class methods for the analysis of food additives by liquid chromatography coupled to tandem mass spectrometry - Detry, Pauline; Willame, Pauline; Van Hoeck, Els; Van Loco, Joris; Goscinny, Séverine (Food additives & contaminants. Part A, Chemistry, analysis, control, exposure & risk assessment, 2022)
Food additives are used in numerous food products and are characterised by various physicochemical properties. In European member states, their use in food is regulated by the European Union. This work aimed to develop an accurate and high-throughput analytical method enabling the simultaneous determination of additives from different functional classes to facilitate controls and generate occurrence data for exposure assessments. The QuEChERS principle was applied due to its ease of implementation and flexibility to adjust to various food matrices. However, very polar substances could not be extracted with sufficient recoveries. Consequently, an alternative basic methanol sample-preparation methodology was developed. After sample preparation, the obtained extracts were analysed using ultra-high-performance liquid chromatography coupled to tandem mass spectrometry (UHPLC-MS/MS). Overall, the developed methodology allowed the quantification of 27 additives from the functional classes of colours, sweeteners, preservatives, and antioxidants in various foods (e.g. beverages, dairies, processed meals). The methods were also validated in terms of selectivity, linearity, matrix effect, limit of quantification, accuracy, repeatability, and intra-laboratory reproducibility. Finally, the methods were successfully applied to eighty-four actual samples. All additives were found below authorised levels. However, irregularities were spotted in labelling.